THE LEVEL OF UNDERSTANDING OF THE NATURE OF SCIENCE FOR PHYSICS TEACHERS AND THE RELATIONSHIP OF THAT EXPERIENCE WITH ACADEMIC QUALIFICATION - Alswelmyeen, Monther Bsharh; Al olimmat, Abeer Rashed (European Scientific Journal, ESJ, 2013)
This study aims to determine the level of the understanding of the nature of Science for physics Teachers and its relation with experience and Academic qualifications. The application of test was applied on a sample chosen randomly consists of (52) physics teachers in Jordan. The study results revealed a low level of understanding of the nature of science in physics teachers and the lack of significant differences in understanding the level of the nature of science as a whole due to the variable of teaching experience, and also found statistically significant differences in the assumptions of science and for the longest teaching experience. the study also showed statistically significant differences in determining the level of understanding of the nature of science, due to the academic qualification and in favor of a higher qualification. The study recommended the need for the inclusion of issues and attitudes a appropriate educational programs in pre-service teacher preparation, and held training sessions for them during their service, in order to enable them understand the nature of science, and finally emphasis on the role of educational supervision in this area.